THE COMPARISON OF THE EFFECTIVENESS OF SULPHASALASINE IN PATIENTS WITH PERIPHERAL AND AXIAL INVOLVEMENT - Ece Kaptanoğlu; Çınar Yıldırım; Cahit Kaçar; Tiraje Tuncer; Aker Akyokuş (Archives of Rheumatology, 2001)
Sulphasalasine (SS) is known to be an effective and safe disease modifying drug in seronegative spodyloarthropathies (SpA). This study was planned to investigate the effectiveness of SS on peripheral and axial involvement. A total of 41 patients were involved in the study, being 11 female and 30 male. The diagnosis of the patients, family history, extra-articular involvement, early morning stiffness, VAS, adverse drug reactions of the SS, compliance of the patients to SS, the ratio of the patients’ benefit from SS, and the other drugs were recorded. The affected and active joints were determined by physical examination. The laboratory parameters like complete blood count, ESR, CRP, liver and kidney function tests, urinary analysis and HLA-B27 tissue antigen which could reflect the activity of the disease and adverse drug reactions were studied. Physical examination and laboratory evaluation were performed before the SSwas given and at the 4th month of the treatment. Regarding the whole group, clinical effectiveness was supported by the statistically significant differences between the values of active joint count, early morning stiffness, and VAS (p<0,05) before the treatment and at the 4th month of treatment. Among the 17 patients with peripheral involvement, there was improvement in the active joint count, early morning stiffness, and VAS after the treatment whereas there was improvement in active joint count and VAS in the group without peripheral involvement (p<0,05). In conclusion; SSZ seems to be effective in patients either with or without peripheral involvement.